2018
DOI: 10.1002/elps.201800198
|View full text |Cite
|
Sign up to set email alerts
|

Revisit of wall‐induced lateral migration in particle electrophoresis through a straight rectangular microchannel: Effects of particle zeta potential

Abstract: Previous studies have reported a lateral migration in particle electrophoresis through a straight rectangular microchannel. This phenomenon arises from the inherent wall-induced electrical lift that can be exploited to focus and separate particles for microfluidic applications. Such a dielectrophoretic-like force has been recently found to vary with the buffer concentration. We demonstrate in this work that the particle zeta potential also has a significant effect on the wall-induced electrical lift. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(90 reference statements)
2
5
0
Order By: Relevance
“…Liu et al. further studied the wall‐induced electrokinetic focusing of four types of 10 µm diameter polystyrene particles from Sigma, Bangs, Thermo, and Duke, respectively, in 1 mM phosphate buffer through the same straight rectangular microchannel under varying DC electric fields (Fig. B).…”
Section: Straight Microchannels With Uniform Cross Sectionsmentioning
confidence: 99%
“…Liu et al. further studied the wall‐induced electrokinetic focusing of four types of 10 µm diameter polystyrene particles from Sigma, Bangs, Thermo, and Duke, respectively, in 1 mM phosphate buffer through the same straight rectangular microchannel under varying DC electric fields (Fig. B).…”
Section: Straight Microchannels With Uniform Cross Sectionsmentioning
confidence: 99%
“…For instance, the micro-detection and therapy of bone crack by diffusiophoresis is a good demonstration as the injured or ill human tissues often release specific chemicals [5]. Indeed, although electrophoresis is still the major workhorse for now in various practical applications utilizing electrokinetic flows [6][7][8][9], diffusiophoresis is coming from behind with a fast pace, especially in the field of drug delivery with the reasons mentioned above [10][11][12][13]. In particular, many important experimental studies were reported by Shin et al recently to broaden the potential practical applications of diffusiophoresis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fluid elasticity effect was demonstrated to tune the lateral particle migration in the electro‐hydrodynamic flow of polyethylene oxide (PEO) solutions, which can be opposite or similar to that in a Newtonian fluid as the polymer concentration is varied [35–38]. In addition, the fluid shear thinning effect was found to direct particles in the electroosmotic flow of xanthan gum (XG) solution toward the microchannel walls [39], opposite to the wall‐induced centerline focusing effect in a Newtonian fluid [40].…”
Section: Introductionmentioning
confidence: 99%